Infrastructure, trade and growth in selected ASEAN countries - Mohd Mahyideen, Jamilah (2015)
Infrastructure is widely recognized as an important ingredient for development and economic growth. However, the significance of infrastructure goes far beyond its impact on growth. Infrastructure and its related services also play a crucial role in international trade flows, particularly after substantial tariff reductions. This study’s main objective is to examine the influence of infrastructure on economic growth and trade flows in ASEAN countries. Specifically, we examine the effects of infrastructure quality and quantity on economic growth by applying the pooled mean group (PMG) estimator. Disentangling the effects of quantity and quality of infrastructure allows policy makers to evaluate the mechanism of transmission from infrastructure investment to economic growth and identify the potential growth benefits they can contribute. After differentiating infrastructure into quantity and quality of infrastructure, we assess the impact of infrastructure quantity in three sectors:transportation, ICT, and energy. Transport infrastructure, as captured by four indicators, is found to be significant in terms of economic growth, and railway lines and road networks appear to be the most influential. To measure ICT infrastructure, we use proxies such as number of fixed lines, mobile phone subscriptions, and internet users. The results provide empirical evidence of the positive effects of telecommunications on growth. Energy infrastructure is also found to have a significant impact on growth when tested with indicators such as electric power consumption per capita, energy use per capita, and energy production. Regarding quality-related measures, we use such variables as percentage of the road network that is paved and electric power transmission and distribution losses as a percentage of GDP. The results show that both quality-related infrastructure variables are important in influencing economic growth in ASEAN countries. In response to a growing interest in the role of infrastructure in facilitating trade, this study investigates the impact of hard and soft infrastructure on trade flows using a gravity model extended with infrastructure variables. We focus not only on the influence of physical infrastructure on trade but also address the role of soft infrastructure. Various indicators from different types of infrastructure, such as those in the transport, energy, and telecommunication sectors, are used and estimated using static models. The model is estimated by using the fixed effects model (FEM) and the random effects model (REM). We find that trade flows increase with improvement in hard infrastructures in all three sectors. In relation to soft infrastructure, we estimate the effects on trade flows of the number of documents and days taken to export by using Fixed Effect Vector Decomposition (FEVD). The results show that soft infrastructure reforms can improve trade flows. This study also analyses the effects of transport infrastructure on sectoral trade flows based on the Standard International Trade Classification (SITC) Rev.3. We include three types of transportation: land transport, sea transport, and air transport. The findings show that different types of transport infrastructure affect sectoral trade flows differently. The study’s empirical results suggest that both quantity and quality of infrastructure contribute positively to ASEAN economic growth. Our findings also confirm the contribution of hard and soft infrastructure in increasing trade flows in the absence of tariff barriers.